Bible Witness in Black Churches - Baker-Fletcher, G. author. aut Link
X, 191 p.
Keywords: Baker-Fletcher explores the Bible as a uniquely authoritative text within the context of Black church worship and service to the world, as well as analysing the Bible's central role in three forms of witness: translation, proclamation, and empowerment.